2018
DOI: 10.3354/meps12663
|View full text |Cite
|
Sign up to set email alerts
|

Short-term processing of ice algal- and phytoplankton-derived carbon by Arctic benthic communities revealed through isotope labelling experiments

Abstract: Benthic ecosystems play a significant role in the carbon (C) cycle through remineralization of organic matter reaching the seafloor. Ice algae and phytoplankton are major C sources for Arctic benthic consumers, but climate change-mediated loss of summer sea ice is predicted to change Arctic marine primary production by increasing phytoplankton and reducing ice algal contributions. To investigate the impact of changing algal C sources on benthic C processing, 2 isotope tracing experiments on 13 C-labelled ice a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 142 publications
0
4
0
Order By: Relevance
“…centimeters of the sediment (Aller and Aller, 1992;Piot el al., 2014;Aschenbroich et al, 2017;Mäkelä et al, 2018). Therefore, we suggest that also the smaller benthic fractions should be identified in future studies on Arctic deep infaunal activity in order to find better infauna variables for explaining the bioturbation measurements.…”
Section: Bioturbation Processes (Sediment Mixing)mentioning
confidence: 67%
“…centimeters of the sediment (Aller and Aller, 1992;Piot el al., 2014;Aschenbroich et al, 2017;Mäkelä et al, 2018). Therefore, we suggest that also the smaller benthic fractions should be identified in future studies on Arctic deep infaunal activity in order to find better infauna variables for explaining the bioturbation measurements.…”
Section: Bioturbation Processes (Sediment Mixing)mentioning
confidence: 67%
“…Significant correlation to Chl a (but not to C org ) was also documented for benthic fluxes in Skagerrak and for SCOC in Arctic seas reviewed by Bourgeois et al (2017) and oligotrophic Aegean Sea . The fundamental role of the C org origin for short-term benthic carbon processing was also indicated by stable isotope tracer experiments (Mäkelä et al, 2018) and bioturbation response after phytopigment addition (Morata et al, 2015). Grebmeier and McRoy (1989) demonstrated that the amount of labile organic material, rather than temperature, drove enhanced sediment oxygen uptake rates in Arctic sediments.…”
Section: 1029/2019jg005140mentioning
confidence: 93%
“…Biomass-weighting isotopic indices reduces the influence of less abundant species so that trophic diversity is not erroneously inflated by rare species feeding at the margins of available organic matter sources. Many benthic species can exhibit substantial feeding plasticity, and thus likely derive their carbon from the most readily available sources (Renaud et al 2007;North et al 2014;Mäkelä et al 2018). If this is the case, isotopic diversity (a relative measure) could exhibit low regional variability despite significant differences in the importance of isotopically-distinct organic matter sources to benthic communities in the Canadian Beaufort Sea and Amundsen Gulf (Stasko et al 2018b).…”
Section: Discussionmentioning
confidence: 99%